Analysis of the incidence of adverse events related to the administration of dipyrone. Issue 2 (April 2018) - González-Cárdenas, Victor Hugo; Laverde-Gaona, Luis A.; Cabarique-Serrano, Sergio H.; Cháves-Rojas, Nataly; Reina-Sierra, Jorge A.; Infante, Juan S.; Quiroz-Díaz, Laura M.; Meneses, Victor D.
Abstract: Introduction: Notwithstanding the widespread use of dipyrone, its association with adverse events has reduced its clinical use, with Agranulocytosis being the most studied adverse event, and apparently of primary clinical impact. Studies in Latin America have disputed these claims. Objective: To analyze the incidence and reports of adverse events associated with the use of dipyrone in a high complexity hospital. Materials and methods: Descriptive observational study of an incident cohort. Population: Patients receiving dipyrone during their hospital stay. Quantitative analysis of incidents and description of dipyrone-associated adverse events. Results: Incidence of global adverse events = 0.3% (in 48, 946 doses of dipyrone prescribed to 2747 patients). No cases of Agranulocytosis. A total 100% non-severe adverse events. (All were associated with toxidermia). Conclusion: A low incidence of dipyrone-associated adverse events is reported. Optimal reporting of institutional adverse events is controversial, and the recommendation is to measure any adverse events with a more rigorous follow-up of patients using dipyrone, and a clear and specific standardization of the guidelines for improved prescription and medical control. Abstract : Supplemental Digital Content is available in the text